Development of educational kit using the basic optical communication system / Nordin Mat Zain and Ahmad Masdi - Mat Zain, Nordin; Masdi, Ahmad (1995)
This educational kit is developed to provide an understanding of the fundamental principles of optical fibre at the college or school level. It is a communication by transmission of light through ultrapure fibre. There are three major parts perform this task of communication: a light source, an optical fibre and a light detector or receiver. Basically, the system simply converts an electrical signal to an infrared light signal, launches or transmits this light signal onto the optical fibre by total internal reflection and then captures the signal on the other end where it converts it to an electrical signal. The heart of this kit is specially designed one-way communication system using microphone and speaker. The use of standard laboratory equipment along with this kit are required. For examples oscilloscope, wave-form generator, voltmeter and spectrum analyser.